TERAKOTA MASA SEJARAH DI INDONESIA: FUNGSI DAN TEKNOLOGINYA - Nurhadi Rangkuti (BRIN, 2001)
The period of history in Indonesia, begins with the existence of writings on stone originating from India, with the Pallava letters, starting from the IV-V century AD. In this article, we limited the observation of terracotta in historical times, since the influence of India, especially Hinduism-Buddhism, until the time of the widespread influence of Islam in Indonesia in the XVI century AD. This limitation is deliberately carried out because the material of this writing is derived from the results of terracotta found at several archaeological sites dating from these periods (historic sites). To enrich information about traditional terracotta, the traditions of making terracotta by several ethnic groups in Indonesia are described.